Legal prevention against illegal export of cultural heritage - Klimczyk, Agata (Journal of Education, Health and Sport, 2017)
The aim of the work is to present legal prevention against illegal exportof cultural heritage. The author has used: the method of legal analysis, historical-legal method and literature study.This paper shows a problematic subject increasing the scale of cultural heritage export. It was showed prevent measures: export license, multiple individual and temporary permits. Attention was paid to the conditioning of the process through the cultural identity and social awareness. References were made to those that affected to this paper.